Professional Career of Women Graduates in Computing in Costa Rica: a Generational Study - Calderón, Marta (2017)
The evolution in women´s professional career in computing has been studied very little. In a previous study (LAWWCC 2016) we reported results of an exploratory study that aimed to characterize the professional development model of people that studied Computer Sciences in Costa Rica, in terms of roles and industrial sectors with which they began their professional career and in which they report are currently working.. Surprisingly, no important gender differences were depicted amongst men and women. As a result, some valid concerns were raised regarding the question: do the results represent the behavior of women in all professional career stages? As a result, in this study, results are now grouped by generations. The aim of this study is to determine whether there are differences in these variables in the professional career evolution for different generations. Results are obtained from an online survey responded by 166 women professionals in Computer Sciences. Women are grouped in four generational categories: baby boomers, generation X, young and mature millennials. The main finding of this research is that the professional evolution of women, with respect to the role and sector in which they perform, revel different behaviors for women of different generations.